Enterprise Architecture untuk Industri Truk Logistik di Indonesia - bayu Yasa Wedha (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
As one of the largest archipelagic countries in the world, Indonesia has more than 17,000 islands and by 2020 the population will reach 270.20 million people. Looking at the geographical conditions and population, the logistics industry is an industry that faces many challenges, especially for logistics companies to achieve efficiency, security and profit. For this reason, this research is focused on designing enterprise architecture for the logistics truck industry, in order to support the achievement of company targets. In this study, the business model is described in the business model canvas, from nine business aspects into a single entity with the company's goals. Anterprice architecture is visualized using elements from the Archimate Core Framework to get an integrated enterprise system result between business elements, data and application elements, as well as technology elements. Based on interviews with experts, this study focuses on 3 main sources of income, namely; revenue from regular delivery of goods, revenue from special delivery of goods (project) and income from transport of waste and chemicals. The results of this study are enterprise architecture in the logistics truck industry along with modeling in Archimate. This research is expected to provide input for logistics truck business players in developing and utilizing information technology in order to survive and increase competitiveness in global competition.